Expressive Uses of Proper Names as Units of Measure in the Current Informal Online Discussion about Politics in Poland - Góralczyk, Iwona (Acta Neophilologica, 2020)
This study offers a cognitive linguistic account of a few remarkably innova-tive uses of proper names to denote units of measure in utterances related to current political issues in Poland, which are delivered with ironic, sarcastic or humorous intent (such as jachiry and ziemce). The novel words, which are all nonce-formations, are minor conversions. They occur preceded by numerals and are pluralised. The coinages creatively elaborate on the morphological and semantic pattern utilised in scientific terminological eponyms (such as niutony and bubnoffy). The focus of this contribution is placed on metonymies and metaphors that motivate the form and content of the coinages.